Restoration of antitumor immunity through anti-MICA antibodies elicited with a chimeric protein. Issue 1 (8th June 2020) - Torres, Nicolas; Regge, María Victoria; Secchiari, Florencia; Friedrich, Adrián David; Spallanzani, Raúl Germán; Raffo Iraolagoitia, Ximena Lucía; Núñez, Sol Yanel; Sierra, Jessica Mariel; Ziblat, Andrea; Santilli, María Cecilia; Gilio, Nicolás; Almada, Evangelina; et al.
Abstract : Background: Natural killer and cytotoxic CD8 + T cells are major players during antitumor immunity. They express NKG2D, an activating receptor that promotes tumor elimination through recognition of the MHC class I chain-related proteins A and B (MICA and MICB). Both molecules are overexpressed on a great variety of tumors from different tissues, making them attractive targets for immunotherapy. However, tumors shed MICA and MICB, and the soluble forms of both (sMICA and sMICB) mediate tumor-immune escape. Some reports indicate that anti-MICA antibodies (Ab) can promote the restoration of antitumor immunity through the induction of direct antitumor effects (antibody-dependent cell-mediated cytotoxicity, ADCC) and scavenging of sMICA. Therefore, we reasoned that an active induction of anti-MICA Ab with an immunogenic protein might represent a novel therapeutic and prophylactic alternative to restore antitumor immunity. Methods: We generated a highly immunogenic chimeric protein (BLS-MICA) consisting of human MICA fused to the lumazine synthase from Brucella spp (BLS) and used it to generate anti-MICA polyclonal Ab (pAb) and to investigate if these anti-MICA Ab can reinstate antitumor immunity in mice using two different mouse tumors engineered to express MICA. We also explored the underlying mechanisms of this expected therapeutic effect. Results: Immunization with BLS-MICA and administration of anti-MICA pAb elicited by BLS-MICA significantly delayed the growth of MICA-expressing mouse tumors but not of control tumors. The therapeutic effect of immunization with BLS-MICA included scavenging of sMICA and the anti-MICA Ab-mediated ADCC, promoting heightened intratumoral M1/proinflammatory macrophage and antigen-experienced CD8 + T cell recruitment. Conclusions: Immunization with the chimeric protein BLS-MICA constitutes a useful way to actively induce therapeutic anti-MICA pAb that resulted in a reprogramming of the antitumor immune response towards an antitumoral/proinflammatory phenotype. Hence, the BLS-MICA chimeric protein constitutes a novel antitumor vaccine of potential application in patients with MICA-expressing tumors.